ADMINISTRASI SURAT BERBASIS MICROSOFT ACCESS PADA BPJS KETENAGAKERJAAN KANTOR WILAYAH JAWA TIMUR - Yuniar Farida; Latifatun Nadya Desinaini (Unit Publikasi Ilmiah, P3M Politeknik Negeri Bali, 2021)
The role of technology in an institution is beneficial for any activities, especially in managing documents administration, which is now most of the company used digital archive systems. That's because the manual archive system is considered less effective and efficient, where it takes a lot of space and time to search for document archives. Microsoft Access is a windows-based database processing program with Visual Basic for Application (VBA), commonly used to create a windows-based application. The purpose of this paper is to make an administration letter and archives system based on Microsoft Access. The results of this design have passed the trial process for approximately two weeks and received a positive response. The system design can be run well, and its functions correctly without errors. So it can help the secretary or other employees to manage all documents (letters and archives) more accessible and faster.